Compound Heterozygous PIGS Variants Associated With Infantile Spasm, Global Developmental Delay, Hearing Loss, Visual Impairment, and Hypotonia - Zhang, Lily; Mao, Xiao; Long, Hongyu; Xiao, Bo; Luo, Zhaohui; Xiao, Wenbiao; Jin, Xingbing (Frontiers in Genetics, 2020)
Glycosylphosphatidylinositol (GPI) is a membrane anchor for cell surface proteins. Inherited GPI deficiencies (IGDs) are a new subclass of congenital disorders of glycosylation (CDGs). Phosphatidylinositol glycan class S (PIGS) is a subunit of the GPI transamidase which plays important roles in many biological processes. In this study, we present a Chinese boy with infantile spasms (IS), severe global developmental delay, hearing loss, visual impairment (cortical blindness), hypotonia and intellectual disability, whose whole-exome sequencing (WES) identified compound heterozygous variants in PIGS(MIM: 610271) : c.148C>T(p. Gln50*) and c.1141_1164dupGACATGGTGCGAGTGATGGAGGTG(p.Asp381_Val388dup). Flow-cytometry analyses demonstrated that the boy with PIGS variants had a decreased expression of GPI-APs. This study stresses the importance of including the screening of PIGS gene in the case of pediatric neurological syndromes, and reviews the clinical features of PIGS-associated disorders.